1998
DOI: 10.1143/jjap.37.486
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Intrinsic Josephson Junctions in a Thin Stack on Bi-2223 Thin Films

Abstract: Micro groove machining is an important task in the fabrication of microdevices. Modern microdevices need metal micromachining techniques such as electro-discharge machining (EDM) and lasers. Micro EDM is a versatile technique for machining electrically conductive materials to make components for microsystem technologies. However, it is generally considered a slow process, because the material removal rate (MRR) is relatively low compared to other machining processes. In this paper, we propose a method to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The flatness of the I-V curve envelope indicates that the stacks in our array are quite homogenous, although in any particular stack the more junctions are biased at voltage states the lower the critical currents will be. We attribute the latter phenomenon to Joule heating and quasiparticle injection 3,4 . From the I-V curves in Fig.3, the total number of junctions in this 256-stack array is estimated to be about 11,000 11 .…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The flatness of the I-V curve envelope indicates that the stacks in our array are quite homogenous, although in any particular stack the more junctions are biased at voltage states the lower the critical currents will be. We attribute the latter phenomenon to Joule heating and quasiparticle injection 3,4 . From the I-V curves in Fig.3, the total number of junctions in this 256-stack array is estimated to be about 11,000 11 .…”
mentioning
confidence: 94%
“…Although one can easily obtain hundreds or thousands of junctions in one stack, with so many junctions it can be sometimes difficult to avoid performance deviations, to have all of them phase locked to external irradiation, and to distribute the applied power evenly among them. Besides, precautions should be taken to prevent junctions or their superconductivity from being damaged by Joule heating or quasiparticle injection 3,4 . Thus, one of the major efforts in the area has been to reduce, or to limit, the junction number in a stack in a well-controlled way.…”
mentioning
confidence: 99%
“…The V,'s for thin stacks were sensitive to the number of stacked junctions [8]. The peculiar 'back-bending' structure with a negative differential resistance near the gap edge in I-V characteristics, as reported by many researchers [1]- [3], was observed for the stacks with -20 or more junctions.…”
Section: A Superconducting Gap Propertiesmentioning
confidence: 65%
“…SEM and AFM analysis revealed that the prepared films were composed of large-sized crystal grains (typically -4pm x -4pm) and the roughness on a grain was within half of a unit cell height, -1.8 nm [4]. We also examined the prepared films by cross-sectional TEM, which exhibited homogeneous lattice images of the Bi-2223 phase with 1.8-nm periodicity in the c-direction near the surface of the film [8].…”
Section: Methodsmentioning
confidence: 99%
“…Many fabrication methods have been applied to fabricate the devices with smaller sizes Latyshev, 1997). However, conventional until now the size of the smallest pattern was only 2×2 μm 2 was achieved with a lithography technique (Odagawa et al, 1998). Three dimensional as an alternative approach, focused-ion-beam (FIB) etching technique is the best choice for the micro/nano scale patterning.…”
Section: Introductionmentioning
confidence: 99%